Highly stretchable and sensitive strain sensors using nano-graphene coated natural rubber - S. Tadakaluru (2018)
© 2017 Institute of Materials, Minerals and Mining Published by Taylor & Francis on behalf of the Institute. Flexible, stretchable and wearable sensors are needed for the human motion detection. Here, a highly stretchable and sensitive strain sensor is fabricated based on the coating of nano-graphene platelets on natural rubber by simple dry coating process. The gauge factors are adjustable in the ranges of 0.78–52.53 depended on the preparation conditions and strain state. The sensors showed a high stretchability up to 750% and high durability of 1500 stretching–releasing cycles. The stretchable strain sensors are capa ble of detecting a bending fingers and the pulse of radial artery on the wrist. In addition, a smart glove made form five independent strain sensors was created. The data of the glove finger motions are used to control an avatar robotic hand.